2019
DOI: 10.1146/annurev-food-032818-121738
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: Recent Advances in the Development of Strategies to Improve Oral Bioavailability

Abstract: Substantial human and preclinical studies have shown that curcumin, a dietary compound from turmeric, has a variety of health-promoting effects including but not limited to antioxidant, antimicrobial, anti-inflammatory, and anticancer actions. However, curcumin has poor bioavailability, and high doses of curcumin are usually needed to exert its health-promoting effects in vivo, limiting its applications for disease prevention. Here, we discuss the health-promoting effects of curcumin, factors limiting its bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 133 publications
0
100
0
Order By: Relevance
“…As already mentioned, the major and urgent issue in curcumin consumption by itself is related to its poor bioavailability. This issue is due to an unfavorable pharmacokinetics (ADMET) profile characterized by low serum levels, limited tissue distribution, apparent rapid metabolism, and a short half-life (Anand et al, 2007;Sanidad et al, 2019). Extensive efforts were accomplished in the never-ending research of innovative and valid strategies to solve these limits.…”
Section: Agro-industrial Procedures To Offset Curcumin Instability Anmentioning
confidence: 99%
“…As already mentioned, the major and urgent issue in curcumin consumption by itself is related to its poor bioavailability. This issue is due to an unfavorable pharmacokinetics (ADMET) profile characterized by low serum levels, limited tissue distribution, apparent rapid metabolism, and a short half-life (Anand et al, 2007;Sanidad et al, 2019). Extensive efforts were accomplished in the never-ending research of innovative and valid strategies to solve these limits.…”
Section: Agro-industrial Procedures To Offset Curcumin Instability Anmentioning
confidence: 99%
“…Some studies have shown that curcumin may also undergo autoxidation under physiological pH conditions [ 3 ]. Despite these potential degradation mechanisms, a rat study reported that around 90% of ingested curcumin remained in the gastrointestinal tract (GIT) after exposure to the stomach and small intestine conditions for 30 min, suggesting that its degradation was relatively slow within the gut [ 66 ]. The bioaccessibility and chemical stability of curcumin can be increased by encapsulating it within a lipid phase, such as a bulk or emulsified oil [ 50 , 67 ].…”
Section: Factors Affecting Curcumin’s Applicationmentioning
confidence: 99%
“…After absorption, curcumin enters the bloodstream and is rapidly distributed throughout the body, resulting in it being located in many tissues at detectable levels, including the liver, kidney, colon, brain, heart, lung, and spleen [ 66 , 72 , 85 , 86 , 87 ]. For instance, a rat study reported that a small amount of curcumin was found in the liver and kidney soon after oral administration, while about 38% was present in the large intestine after 24 h [ 66 ].…”
Section: Factors Affecting Curcumin’s Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, some nutraceuticals seem to improve NAFLD, when prescribed on top of therapeutic lifestyle changes [23]. For instance, Silymarin, a mixture of flavolignans extracted from Sylibum marianum, acting through different mechanisms and complex biological interactions has largely shown to improve the prognosis of patients affected by chronic liver diseases [24].The actions of berberine, curcumin and coenzyme q10 are related to the improvement of levels of indirect markers of hepatosteatosis (Hepatic Steatosis Index, Lipid Accumulation Product) for short-term supplements (2-4 months), even if each of these nutraceuticals showed any bioavailability problems [25][26][27]. In accordance with the parallel-hit hypothesis, stating that the development of liver disease involves a group of simultaneous alterations in the organism, combinations of different bioactive compounds that act against complementary targets have been examined [28].…”
Section: Introductionmentioning
confidence: 99%